Resin particles, toner, developer, and toner storage unit

The use of propylene glycol, ester wax, and PET in resin particles addresses the environmental and durability issues of toners by eliminating dispersants, resulting in durable and eco-friendly toner solutions.

JP2025007589APending Publication Date: 2025-01-17RICOH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023109090
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-03
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing toners face challenges in reducing environmental impact due to the use of petroleum-derived dispersants and plant-derived resins, which compromise toner strength and durability.

Method used

Resin particles are developed using a combination of propylene glycol, ester wax, and polyethylene terephthalate (PET), eliminating the need for dispersants and incorporating recycled PET to enhance durability and environmental friendliness.

Benefits of technology

The combination results in highly durable resin particles with reduced environmental impact, maintaining strength and improving fixing properties while minimizing the use of petroleum-derived components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007589000003
    Figure 2025007589000003
  • Figure 2025007589000001
    Figure 2025007589000001
  • Figure 2025007589000002
    Figure 2025007589000002
Patent Text Reader

Abstract

To provide resin particles with a low environmental load and high durability.SOLUTION: The present invention relates to a resin particle comprising a binder resin containing a polyester resin, and a release agent. The binder resin contains polyethylene terephthalate as a component of the polyester resin and propylene glycol as a diol component constituting the binder resin. The release agent is an ester wax.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to resin particles, a toner, a developer, and a toner storage unit. [Background technology]

[0002] In recent years, there has been a demand for toners that place less of a burden on the environment. To this end, measures such as reducing the energy used in production and using plant-derived resins as binder resins are being considered.

[0003] It is known that in recent toners, release agents are added to improve fixation, but in this case, not only the release agent but also a dispersant for the release agent is added to the resin particles to disperse the release agent in the toner. However, dispersants are petroleum-derived components and have a large environmental impact, so it is desirable to reduce the amount of dispersant used.

[0004] Patent Document 1 proposes using a plant-derived resin in a polymerized toner that requires less energy to produce, but the use of a plant-derived resin reduces the strength of the toner, and the quality is not satisfactory. Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide resin particles which are environmentally friendly and highly durable. [Means for solving the problem]

[0006] One aspect of the present invention is Resin particles containing a binder resin and a release agent, The binder resin contains a polyester resin, The polyester resin contains polyethylene terephthalate as a component, The binder resin contains propylene glycol as a diol component, The release agent is an ester wax. These are resin particles. Effect of the Invention

[0007] According to the present invention, it is possible to provide highly durable resin particles which impose less of a burden on the environment. [Brief description of the drawings]

[0008] [Figure 1] 1 is a schematic diagram illustrating an example of a process cartridge that contains a toner according to an embodiment of the present invention and is detachably mountable to an image forming apparatus; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The resin particles according to the present invention will be described in detail below. The present invention is not limited to the following embodiments, and can be modified as appropriate without departing from the gist of the present invention. In addition, in this specification, "to" indicating a numerical range means that the numerical values ​​before and after it are included as the lower and upper limits, unless otherwise specified. Although the present invention relates to resin particles, the present invention will be described below by taking toner as an example of resin particles, and therefore, hereinafter, resin particles will be referred to as toner.

[0010] As a result of extensive research into resin particles used as toner, the inventors of the present application have found that by combining propylene glycol, ester wax, and polyethylene terephthalate (hereinafter referred to as PET), it is possible to obtain resin particles that are highly durable and have a low environmental impact. Specifically, the combination of propylene glycol and ester wax makes it possible to disperse a release agent in the resin particles without using a dispersant, and also allows the use of recycled PET, thereby reducing the environmental impact.

[0011] <Toner> The toner of the present invention is characterized in that the release agent is an ester wax, the binder resin contains at least a polyester resin, the polyester resin contains PET as a component, and the binder resin contains propylene glycol as a diol component.

[0012] The toner of the present invention preferably has a core-shell structure, which increases the strength of the toner surface and improves the durability of the toner.

[0013] In the toner of the present invention, the ratio of the length of the line occupied by the release agent to the total length of the circumference of the outermost surface of the toner is preferably 5% or less, more preferably 3% or less. If it exceeds 5%, the strength of the toner is reduced due to the release agent present on the surface.

[0014] The propylene glycol that is a raw material of the toner of the present invention is preferably non-petroleum derived. By using non-petroleum derived propylene glycol as a raw material, the environmental impact of the toner can be reduced.

[0015] The PET, which is the raw material of the toner of the present invention, is preferably a recycled product. By using recycled PET as a raw material, the environmental impact of the toner can be reduced. In addition to recycled products, off-spec fiber waste or pellets may also be used.

[0016] The main raw materials of the toner of the present invention will be described below.

[0017] <Ester wax> The toner of the present invention contains an ester wax. The ester wax used in the present invention has a sharper carbon number distribution than natural paraffin wax and microcrystalline wax that are used as raw materials for existing toners, and therefore can improve the durability of the toner.

[0018] Generally, ester wax is synthesized from a higher alcohol component and a higher carboxylic acid component. These higher alcohol components and higher carboxylic acid components are usually obtained from natural products, and generally consist of a mixture having an even number of carbon atoms. When these mixtures are directly esterified, multiple by-products are produced in addition to the desired ester compound, which tends to adversely affect the properties of the toner. In such a case, an ester wax with an adjusted carbon number distribution can be obtained by purifying the raw materials and products using solvent extraction or reduced pressure distillation.

[0019] The ester wax has a high affinity with the polyester resin containing propylene glycol, and the ester wax is well dispersed in the resin particles.

[0020] The melting point of the ester wax is not particularly limited and can be appropriately selected according to the purpose, but is preferably 50°C to 120°C, more preferably 60°C to 90°C. If the melting point is 50°C or higher, the ester wax can be prevented from adversely affecting the heat-resistant storage stability, and if the melting point is 120°C or lower, the problem of cold offset occurring during fixing at low temperatures can be effectively prevented. The melt viscosity of the ester wax is preferably 5 cps to 1,000 cps, more preferably 10 cps to 100 cps, measured at a temperature 20°C higher than the melting point of the ester wax. If the melt viscosity is 5 cps or higher, the release property can be prevented from decreasing, and if it is 1,000 cps or lower, the effects of hot offset resistance and low-temperature fixability can be fully exhibited. The content of the ester wax in the toner is not particularly limited and can be appropriately selected according to the purpose, but is preferably 0% by mass to 40% by mass, more preferably 3% by mass to 30% by mass. If the content is 40% by mass or lower, the fluidity of the toner can be prevented from deteriorating.

[0021] <Polyethylene terephthalate (PET)> In the present invention, PET is contained as a binder resin. As the PET, a recycled product processed into a flake shape may be used, and the weight average molecular weight (Mw) of the recycled product is about 30,000 to 90,000, but there are no limitations on the molecular weight distribution, composition, manufacturing method, form when used, etc. When synthesizing the polyester resin, the ratio of the recycled PET introduced can be adjusted to adjust the environmental response ratio and toner quality.

[0022] As an alternative to PET, polybutylene terephthalate (PBT) and its recycled products may be used. <Other binder resins> As the binder resin to be used other than PET, amorphous polyester resins which are advantageous for low-temperature fixing are preferred, and among them, linear polyester resins are preferred, and unmodified polyester resins are also preferred.

[0023] The unmodified polyester resin is a polyester resin obtained using a polyhydric alcohol and a polycarboxylic acid or a derivative thereof, such as a polycarboxylic acid, a polycarboxylic anhydride, or a polycarboxylic ester, and is not modified with an isocyanate compound or the like.

[0024] The amorphous polyester resin preferably does not contain a urethane bond or a urea bond.

[0025] The polyhydric alcohol contains at least propylene glycol. By combining this with an ester wax described below, it becomes possible to disperse the release agent in the toner without using a dispersant, and resin particles with low environmental impact can be produced. In addition, by using non-petroleum-derived propylene glycol, the environmental impact can be further reduced.

[0026] The content of propylene glycol in the binder resin is preferably 5% or more based on the total amount of the binder resin.

[0027] The polyhydric alcohol may contain a polyhydric alcohol other than propylene glycol. The polyhydric alcohol is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include diols.

[0028] Examples of the diol other than propylene glycol include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, 1,20-eicosanediol, bisphenol A, alkylene (carbon number 2-3) oxide (average added mole number 1-10) adduct of bisphenol A, hydrogenated bisphenol A, alkylene (carbon number 2-3) oxide (average added mole number 1-10) adduct of hydrogenated bisphenol A, etc. These may be used alone or in combination of two or more.

[0029] Examples of the polycarboxylic acid include dicarboxylic acids.

[0030] Examples of the dicarboxylic acid include saturated aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, and 1,18-octadecanedicarboxylic acid; and aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, terephthalic acid, and naphthalene-2,6-dicarboxylic acid. Further examples include anhydrides of these and lower (carbon number 1 to 3) alkyl esters of these. These may be used alone or in combination of two or more. Among them, it is preferable to contain 50 mol % or more of terephthalic acid in terms of excellent heat resistance storage stability of the resin.

[0031] For the purpose of adjusting the acid value and hydroxyl value, the amorphous polyester resin may contain at least one of a trivalent or higher carboxylic acid and a trivalent or higher alcohol at the end of the resin chain.

[0032] Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, and acid anhydrides thereof.

[0033] Examples of the trihydric or higher alcohol include glycerin, pentaerythritol, and trimethylolpropane.

[0034] The molecular weight of the amorphous polyester resin is not particularly limited and can be appropriately selected depending on the purpose. In the measurement by GPC (gel permeation chromatography), the weight average molecular weight (Mw) is preferably 3,000 to 10,000. The number average molecular weight (Mn) is preferably 1,000 to 4,000. The Mw / Mn is preferably 1.0 to 4.0.

[0035] When the molecular weight is equal to or more than the lower limit, it is possible to suppress a decrease in the heat-resistant storage stability of the toner and in the durability against stress caused by stirring in a developing machine, etc. When the molecular weight is equal to or less than the upper limit, it is possible to suppress an increase in the viscoelasticity of the toner when melted, and to suppress a decrease in the low-temperature fixability.

[0036] The weight average molecular weight (Mw) is more preferably from 4000 to 7000. The number average molecular weight (Mn) is more preferably from 1500 to 3000. The Mw / Mn is more preferably from 1.0 to 3.5.

[0037] The acid value of the amorphous polyester resin is not particularly limited and can be appropriately selected according to the purpose. It is preferably 1 mgKOH / g to 50 mgKOH / g, more preferably 5 mgKOH / g to 30 mgKOH / g. When the acid value is 1 mgKOH / g or more, the toner tends to be negatively charged, and further, when fixed to paper, the affinity between the paper and the toner is improved, and low-temperature fixability can be improved. When the acid value is 50 mgKOH / g or less, it is possible to suppress a decrease in charging stability, particularly charging stability against environmental changes.

[0038] The hydroxyl value of the amorphous polyester resin is not particularly limited and may be appropriately selected depending on the purpose, but is preferably 5 mgKOH / g or more.

[0039] The glass transition temperature (Tg) of the amorphous polyester resin is preferably 40° C. to 80° C., more preferably 50° C. to 70° C. When the glass transition temperature is 40° C. or higher, the toner has sufficient heat-resistant storage stability and durability against stress such as stirring in a developing machine, and also has good filming resistance. When the glass transition temperature is 80° C. or lower, the toner is sufficiently resistant to deformation due to heating and pressure during fixing, and has good low-temperature fixing properties.

[0040] The molecular structure of the amorphous polyester resin can be confirmed by NMR measurement of a solution or solid, as well as X-ray diffraction, GC / MS, LC / MS, IR measurement, etc. -1 and 990±10cm -1 to the δ of olefin CH One method is to detect a resin that does not have absorption due to (out-of-plane bending vibration) as an amorphous polyester resin.

[0041] The content of the amorphous polyester resin is not particularly limited and can be appropriately selected according to the purpose, but is preferably 50 parts by mass to 90 parts by mass, more preferably 60 parts by mass to 80 parts by mass, relative to 100 parts by mass of the toner. When the content is 50 parts by mass or more, the dispersibility of the pigment and the release agent in the toner can be suppressed from deteriorating, and the occurrence of fogging and disturbance of the image can be suppressed. When the content is 90 parts by mass or less, the decrease in low-temperature fixability can be suppressed. When the content is in the above-mentioned more preferred range, it is advantageous in that both high image quality and low-temperature fixability are excellent.

[0042] <Coloring agent> As the colorant of the present invention, known dyes and pigments can be used, for example, carbon black, nigrosine dye, iron black, naphthol yellow S, Hansa yellow (10G, 5G, G), cadmium yellow, yellow iron oxide, yellow ochre, yellow lead, titanium yellow, polyazo yellow, oil yellow, Hansa yellow (GR, A, RN, R), pigment yellow L, benzidine yellow (G, GR), permanent yellow (NCG), Balkan fast yellow (5G, R), tartrazine lake, quinoline yellow lake, anthrazan yellow BGL, isoindolinone. Yellow, red iron oxide, red lead, vermilion, cadmium red, cadmium mercury red, antimony vermilion, permanent red 4R, para red, phisee red, parachloro orthonitroaniline red, lithol fast scarlet G, brilliant fast scarlet, brilliant carmine BS, permanent red (F2R, F4R, FRL, FRLL, F4RH), fast scarlet VD, belkan fast rubin B, brilliant scarlet G, lithol rubin GX, permanent red F5R, brilliant carmine 6B, Scarlet Scarlet 3B, Bordeaux 5B, Toluidine Maroon, Permanent Bordeaux F2K, Helio Bordeaux BL, Bordeaux 10B, Bon Maroon Light, Bon Maroon Medium, Eosin Lake, Rhodamine Lake B, Rhodamine Lake Y, Alizarin Lake, Thioindigo Red B, Thioindigo Maroon, Oil Red, Quinacridone Red, Pyrazolone Red, Polyazo Red, Chrome Vermilion, Benzidine Orange, Perinone Orange, Oil Orange, Cobalt Blue, Cerulean Blue, Alkaline Blue Lake, Peacock Blue - Lake, Victoria Blue Lake, Metal-free Phthalocyanine Blue, Phthalocyanine Blue, Fast Sky Blue, Indanthrene Blue (RS, BC), Indigo, Ultramarine Blue, Prussian Blue, Anthraquinone Blue, Fast Violet B, Methyl Violet Lake, Cobalt Purple, Manganese Purple, Dioxane Violet, Anthraquinone Violet, Chrome Green, Zinc Green, Chromium Oxide, Pyridian, Emerald Green, Pigment Green B, Naphthol Green B, Green Gold, Acid Green Lake, Malachite Green Lake,Phthalocyanine green, anthraquinone green, titanium oxide, zinc oxide, lithopone and mixtures thereof can be used.

[0043] The toner according to the present embodiment can be effectively used as a material for image formation, such as a developer, a toner storage unit, and the like.

[0044] <Developer> The developer according to the present embodiment contains the toner according to one embodiment, and may contain other components, such as a carrier, that are appropriately selected as necessary. This allows the developer to have excellent transferability, chargeability, and the like, and to stably form high-quality images.

[0045] The developer may be a one-component developer or a two-component developer. However, when used in high-speed printers that correspond to the recent improvements in information processing speed, a two-component developer is preferable from the viewpoint of improving the developer life.

[0046] When the toner according to this embodiment is used in a one-component developer, even if the toner is balanced, there is little variation in the particle size of the toner, and toner filming on the developing roller and toner adhesion to components such as blades that thin the toner layer are reduced, resulting in high-quality images being obtained in the developing device.

[0047] When the developer according to the present embodiment is used as a two-component developer, it can be mixed with a carrier and used as a developer. When the toner according to the embodiment is used as a two-component developer, the particle size of the toner is small even if the toner is balanced over a long period of time, and good and stable developability and images can be obtained even when the toner is stirred for a long period of time in a developing device.

[0048] The content of the carrier in the two-component developer can be appropriately selected depending on the purpose, but is preferably 90 parts by mass to 98 parts by mass, and more preferably 93 parts by mass to 97 parts by mass, relative to 100 parts by mass of the two-component developer.

[0049] The developer according to the present embodiment can be suitably used for image formation by various known electrophotographic methods such as a magnetic one-component development method, a non-magnetic one-component development method, and a two-component development method.

[0050] [Career] The carrier is not particularly limited and can be appropriately selected depending on the purpose, but it is preferable that the carrier has a core material and a resin layer (coating layer) that coats the core material.

[0051] (Core material) The material of the core material is not particularly limited and can be appropriately selected according to the purpose. For example, manganese-strontium-based material of 50 emu / g to 90 emu / g, manganese-magnesium-based material of 50 emu / g to 90 emu / g, etc. can be mentioned. In order to ensure image density, it is preferable to use high magnetization materials such as iron powder of 100 emu / g or more, magnetite of 75 emu / g to 120 emu / g. In addition, it is preferable to use low magnetization materials such as copper-zinc-based materials of 30 emu / g to 80 emu / g, because it can reduce the impact of the developer in a standing state on the photoconductor and is advantageous for high image quality. These materials may be used alone or in combination of two or more.

[0052] The volume average particle diameter of the core material is not particularly limited and can be appropriately selected according to the purpose, but is preferably 10 μm to 150 μm, more preferably 40 μm to 100 μm. If the volume average particle diameter is 10 μm or more, the amount of fine powder in the carrier increases, and the magnetization per particle decreases, which can effectively prevent the problem of carrier scattering. On the other hand, if it is 150 μm or less, the specific surface area decreases, which can cause toner scattering, and in full color with many solid parts, the problem of poor reproduction of the solid parts can be effectively prevented.

[0053] (Resin layer) The resin layer can contain a resin and other components as necessary. The resin used in the resin layer can be a known material that can impart the necessary electrostatic property. Specifically, it is preferable to use a silicone resin, an acrylic resin, or a combination of these. In addition, the composition for forming the resin layer preferably contains a silane coupling agent.

[0054] The average thickness of the resin layer is preferably 0.05 to 0.50 μm.

[0055] <Toner storage unit> The toner storage unit according to the present embodiment can store the toner according to the present embodiment. The toner storage unit according to the present embodiment refers to a unit having a function of storing toner, in which the toner is stored. Here, examples of the toner storage unit include a toner storage container (a container containing toner), a developing device, and a process cartridge.

[0056] The toner storage container refers to a container that stores toner.

[0057] The developing device has a means for containing toner and developing the toner.

[0058] The process cartridge is a cartridge that integrates at least an electrostatic latent image carrier (also called an image carrier) and a developing unit, contains toner, and is detachable from an image forming apparatus. The process cartridge may further include at least one selected from a charging unit, an exposure unit, a cleaning unit, etc.

[0059] [One embodiment of the process cartridge] One aspect of the process cartridge according to the present embodiment will be described with reference to Fig. 1. Fig. 1 is a diagram showing an example of the process cartridge according to the present embodiment. As shown in Fig. 1, the process cartridge 200 has a photosensitive drum 10, a corona charger 22 which is a charging unit, a developing device 40, a transfer roller 50, and a cleaning device 60. In the figure, P indicates transfer paper, and L indicates exposure light.

[0060] <Measurement method> [Toner particle size] The toner particle size was measured using a Coulter Multisizer III (manufactured by Coulter, Inc.) The toner particle size was measured as follows.

[0061] First, 2 mL of a surfactant (sodium dodecylbenzenesulfonate, manufactured by Tokyo Chemical Industry Co., Ltd.) was added as a dispersant to 100 mL of the electrolyte. The electrolyte was prepared by using first-class sodium chloride to prepare an approximately 1% NaCl aqueous solution, and ISOTON-II (manufactured by Coulter Corporation) was used. 10 mg of a measurement sample was added as a solid content to the mixture of the electrolyte and the surfactant to obtain an electrolyte in which the sample was suspended. The electrolyte in which the sample was suspended was subjected to a dispersion process using an ultrasonic disperser for approximately 1 to 3 minutes, and the volume and number of toner particles were measured using a Coulter Multisizer III with a 100 μm aperture as an aperture, and the volume distribution and number distribution were calculated. From the obtained distribution, the volume average particle size (Dv) of the toner was obtained.

[0062] [Average particle size, average circularity] In this embodiment, the average particle diameter and the average circularity are measured using, for example, a flow type particle image analyzer FPIA-3000 (manufactured by Sysmex Corporation).

[0063] In a specific measurement method, 0.1 to 0.5 ml of a surfactant, preferably an alkylbenzene sulfonate, is added as a dispersant to 100 to 150 ml of water from which solid impurities have been removed in advance in a container, and about 0.1 to 0.5 g of a measurement sample is further added. The suspension in which the sample is dispersed is subjected to a dispersion treatment for about 1 to 3 minutes with an ultrasonic disperser, and the dispersion concentration is set to 3,000 to 10,000 particles / μL, and the average particle size, average circularity, and standard deviation (SD) of the circularity are measured with the above device.

[0064] However, the particle diameter is the equivalent circle diameter, the average particle diameter is determined based on the equivalent circle diameter (number basis), and the analysis conditions for the flow type particle image analyzer are as follows: Particle size limit: 0.5μm≦circle equivalent diameter (number basis)≦200.0μm Particle shape limit: 0.93<circularity≦1.00 In the present embodiment, the average circularity is defined as follows. (Average circularity) = (perimeter of a circle equal to the projected area) / (perimeter of the projected image)

[0065] [Molecular weight measurement] The molecular weight of each of the components of the toner can be measured, for example, by the following method. Gel permeation chromatography (GPC) measuring device: GPC-8220GPC (manufactured by Tosoh Corporation) Column: TSKgel SuperHZM-H 15cm triple column (Tosoh Corporation) Temperature: 40℃ Solvent: THF Flow rate: 0.35mL / min Sample: 100 μL of 0.15% by mass sample injected Sample pretreatment: The toner is dissolved in tetrahydrofuran (THF) (containing a stabilizer, manufactured by Wako Pure Chemical Industries, Ltd.) at 0.15% by mass, then filtered through a 0.2 μm filter, and the filtrate is used as the sample. 100 μL of the THF sample solution is injected and measured.

[0066] When measuring the molecular weight of a sample, the molecular weight distribution of the sample is calculated from the relationship between the logarithm value and the count number of a calibration curve prepared using several monodisperse polystyrene standard samples. Standard polystyrene samples for preparing the calibration curve are Std. No. S-7300, S-210, S-390, S-875, S-1980, S-10.9, S-629, S-3.0, and S-0.580 of Shodex STANDARD manufactured by Showa Denko Co., Ltd. A refractive index (RI) detector is used as the detector.

[0067] Shell Thickness The thickness of the shell is measured based on an image of a cross section of an ultrathin slice of the toner taken with a transmission electron microscope (TEM).

[0068] The shell thickness is a value calculated from the following formula: The shell thickness value is preferably a value determined by image processing software, but is not limited to the above-mentioned transmission microscope device, image analyzer, and software as long as similar analysis results can be obtained. (Shell thickness) = (average circular equivalent diameter of core-shell type resin particles) / (average circular equivalent diameter of core) Here, the average equivalent circle diameter can be calculated by binarization processing using image software.

[0069] [Observation and measurement using a transmission electron microscope] The toner thus prepared is embedded in an epoxy resin and hardened. Ultrathin sections (approximately 100 nm thick) of the toner are prepared using an ultramicrotome (Leica ULTRACUT UCT, diamond knife used).

[0070] The sample is exposed to ruthenium tetroxide, osmium tetroxide, or another staining agent, and the core and shell layers are differentiated. The exposure time is adjusted appropriately depending on the contrast during observation. The sample is then observed with a transmission electron microscope (JEM-2100, JEOL) at an accelerating voltage of 100 kV. It is also possible to impart compositional contrast by other means such as selective etching, and after such pretreatment, the core and shell layers may be evaluated by observing with a transmission microscope.

[0071] The average equivalent circular diameter of the core-shell type resin particles and the average equivalent circular diameter of the core are calculated by binarizing the observed cross-sectional image using a commercially available image processing software (e.g., Image-Pro Plus, etc.). The cross sections of 20 toner particles are observed to determine the average equivalent circular diameter.

[0072] In the present invention, the toner was embedded in an epoxy resin, sliced ​​into ultra-thin slices of about 100 μm, and stained with ruthenium tetroxide. The cross section of the toner was observed at a magnification of 10,000 times using a transmission electron microscope (JEM-2100, manufactured by JEOL Co., Ltd.) and photographed. 20 photographs (20 toner particles) were evaluated for image quality to measure the circumferential line length of the outermost surface of the resin particle and the line length occupied by the release agent.

[0073] [Analysis of surface resin composition] The presence of PET-derived resin components in the surface layer can be confirmed by a composition analysis of the surface layer using nanoIR as an indicator. The composition can be obtained by acquiring the IR spectrum of the surface layer of the fine particles using an analytical method that combines nanoIR AFM and IR to achieve nanoscale resolution. This analysis makes it possible to identify whether a PET-derived composition is present in the surface layer.

[0074] [Method of analyzing toner components] The glass transition temperature (Tg), melting point, acid value, hydroxyl value, and molecular weight of the amorphous polyester resin, PET or PBT, and release agent in the resin particles, as well as the mass ratio of each of the constituent components in the resin particles may be measured for each component per se, or may be calculated by separating the resin particles obtained by the present invention using GPC or the like and applying the analytical methods described below to each of the separated components. Separation of the individual components in the resin particles by GPC can be carried out, for example, by the following method. In the GPC measurement using chloroform as the mobile phase, the eluate is fractionated using a fraction collector or the like, and the fractions corresponding to the desired molecular weight portion within the full integral of the elution curve are collected. The combined eluate is concentrated and dried using an evaporator or the like, and the solid content is dissolved in a heavy solvent such as deuterated chloroform or deuterated THF, 1 H-NMR measurement is performed, and the ratio of each component in the resin particles in the eluted components is calculated from the integral ratio of each element. Another method is to concentrate the combined eluate, hydrolyze it using sodium hydroxide or the like, and then qualitatively and quantitatively analyze the decomposition products using high performance liquid chromatography (HPLC) or the like to calculate the ratio of each constituent component in the resin particles. In addition, when the method for producing resin particles includes forming base particles of the resin particles while generating an amorphous polyester resin by an elongation reaction and / or a crosslinking reaction between a non-linear reactive precursor and a curing agent, the resin particles obtained by the present invention may be separated by GPC or the like to determine the glass transition temperature (Tg) of the amorphous polyester resin. In addition, an amorphous polyester resin may be synthesized by an elongation reaction and / or a crosslinking reaction between a non-linear reactive precursor and a curing agent, and the glass transition temperature (Tg) of the synthesized amorphous polyester resin may be measured.

[0075] An example of the method for producing the toner of the present invention is described below. Note that the method for producing the toner of the present invention is not limited to the method described below, and any known method can be used as appropriate as long as it satisfies the requirements of the present invention.

[0076] <Resin dispersion liquid preparation process> A resin dispersion liquid is prepared by dissolving or dispersing a binder resin, a colorant, a crosslinking component, an ester wax, etc. The method for preparing the resin dispersion liquid is not particularly limited and can be appropriately selected depending on the purpose, and for example, a method in which raw materials such as a resin are gradually added to ion-exchanged water while stirring, and dissolved or dispersed can be mentioned. For dispersion, a known device can be used, for example, a dispersing machine such as a bead mill or a disk mill can be used.

[0077] <Emulsification process> Next, the resin dispersion obtained in the resin dispersion preparation step is pulverized into fine particles. In the present invention, the resin dispersion is neutralized with an alkali such as sodium hydroxide or aqueous ammonia, and then an aqueous phase containing water, an organic solvent, and a surfactant is added thereto to obtain an emulsified slurry.

[0078] [Organic solvents] The organic solvent is preferably volatile with a boiling point of less than 100° C., since this facilitates subsequent removal of the organic solvent. As such an organic solvent, for example, toluene, xylene, benzene, carbon tetrachloride, methylene chloride, 1,2-dichloroethane, 1,1,2-trichloroethane, trichloroethylene, chloroform, monochlorobenzene, dichloroethylidene, methyl acetate, ethyl acetate, methyl ethyl ketone, methyl isobutyl ketone, methanol, ethanol, isopropyl alcohol, etc. can be used alone or in combination of two or more. When the resin to be dissolved or dispersed in the organic solvent is a resin having a polyester skeleton, it is preferable to use an ester-based solvent such as methyl acetate, ethyl acetate, or butyl acetate, or a ketone-based solvent such as methyl ethyl ketone or methyl isobutyl ketone, since these have high solubility, and among these, methyl acetate, ethyl acetate, and methyl ethyl ketone, which have high solvent removability, are particularly preferred.

[0079] <Solvent removal process> In order to remove the organic solvent from the obtained emulsified slurry, a method can be adopted in which the temperature is gradually raised while stirring the entire system, and the organic solvent in the droplets is completely evaporated and removed. Alternatively, the obtained emulsified slurry can be sprayed into a dry atmosphere while stirring, and the organic solvent in the droplets can be completely removed. Alternatively, the emulsified slurry can be reduced in pressure while stirring, and the organic solvent can be evaporated and removed. The latter two methods can be used in combination with the first method.

[0080] The drying atmosphere into which the emulsified slurry is sprayed generally includes air, nitrogen, carbon dioxide, heated combustion gas, etc., and in particular, various air streams heated to a temperature equal to or higher than the boiling point of the highest boiling point solvent used. The desired quality can be obtained sufficiently by short-term treatment using a spray dryer, belt dryer, rotary kiln, etc.

[0081] By the above method, a colored particle dispersion liquid from which the organic solvent has been removed can be obtained.

[0082] <Agglomeration process> Next, the obtained colored particle dispersion is agitated to aggregate the particles to a desired particle size. To aggregate the particles, existing methods such as adding an aggregating agent or adjusting the pH can be used. When adding an aggregating agent, the agent may be added as is, but it is preferable to add the agent in an aqueous solution, since this can prevent localized high concentration. It is also preferable to gradually add the aggregating salt while monitoring the particle size of the colored particles.

[0083] The temperature of the dispersion during aggregation is preferably near the Tg of the resin used. If the liquid temperature is too low, aggregation does not proceed very well, resulting in poor efficiency, whereas if the liquid temperature is too high, the aggregation rate increases, resulting in the generation of coarse particles and a deterioration in particle size distribution.

[0084] When the target particle size is reached, aggregation is stopped by adding a salt with a low ionic valence or a chelating agent, adjusting the pH, lowering the temperature of the dispersion, adding a large amount of an aqueous medium to dilute the concentration, or the like.

[0085] By the above method, a dispersion of colored aggregated particles can be obtained.

[0086] As the flocculant, a known flocculant can be used, for example, a metal salt of a monovalent metal such as sodium or potassium, a metal salt of a divalent metal such as calcium or magnesium, or a metal salt of a trivalent metal such as iron or aluminum.

[0087] <Fusing process> Next, the obtained aggregated particles are fused by heat treatment to reduce unevenness and to make them spherical. Fusion can be performed by heating the dispersion of the colored aggregated particles while stirring. The temperature of the liquid is preferably near a temperature above the Tg of the resin used.

[0088] <Shelling process> In the production of the toner of the present invention, it is preferable to carry out shell formation.

[0089] The method for forming the shell layer is not particularly limited and can be appropriately selected depending on the purpose. For example, the method for forming the shell layer includes a method in which spherical particles having a desired particle size are produced in a fusion step, and then an amorphous resin is added, and the aggregating step and the fusion step are repeated to form the shell layer.

[0090] By the above method, a toner particle dispersion liquid can be obtained.

[0091] <Cleaning and drying process> The toner particle dispersion obtained by the above method contains sub-materials such as coagulating salts in addition to the toner particles, so washing is carried out in order to extract only the toner particles from the dispersion.

[0092] The washing method of the toner particles includes a centrifugation method, a vacuum filtration method, a filter press method, etc., but is not particularly limited in the present invention. Any of the methods can obtain a cake of toner particles, but if the toner particles cannot be sufficiently washed in one operation, the obtained cake may be dispersed again in an aqueous solvent to form a slurry, and the process of extracting the toner particles by any of the above methods may be repeated. In addition, if washing is performed by the vacuum filtration method or the filter press method, a method of passing the aqueous solvent through the cake to wash out the secondary materials that are incorporated in the toner particles may be adopted.

[0093] The aqueous solvent used for washing is water or a mixed solvent of water and an alcohol such as methanol or ethanol. Considering the cost and the environmental load due to wastewater treatment, it is preferable to use water.

[0094] Since the washed toner particles contain a large amount of the aqueous medium, only the toner particles can be obtained by removing the aqueous medium through drying.

[0095] For the drying method, a dryer such as a spray dryer, a vacuum freeze dryer, a reduced pressure dryer, a stationary shelf dryer, a movable shelf dryer, a fluidized bed dryer, a rotary dryer, or an agitator dryer can be used.

[0096] The dried toner particles are preferably dried until the moisture content is finally reduced to less than 1%. If the dried toner particles are in the form of soft aggregates and cause inconvenience in use, the soft aggregates may be broken down using a device such as a jet mill, a Henschel mixer, a super mixer, a coffee mill, an Oster blender, or a food processor.

[0097] <External addition process> In order to impart fluidity, chargeability, cleaning properties, and the like to the toner particles obtained in this embodiment, inorganic fine particles, polymeric fine particles, cleaning aids, and the like may be added or mixed thereto.

[0098] Specific mixing means include a method in which an impact force is applied to the mixture by blades rotating at high speed, and a method in which the mixture is introduced into a high-speed air current, accelerated, and the particles collide with each other or the composite particles with an appropriate collision plate.

[0099] Examples of equipment include an Angmill (manufactured by Hosokawa Micron Corporation), a modified I-type mill (manufactured by Japan Pneumatic Co., Ltd.) with reduced grinding air pressure, a hybridization system (manufactured by Nara Machinery Works, Ltd.), a Cryptron system (manufactured by Kawasaki Heavy Industries, Ltd.), and an automatic mortar.

[0100] [External additives] The primary particle diameter of the inorganic fine particles is preferably 5 nm to 2 μm, and more preferably 5 nm to 500 nm. The specific surface area as measured by the BET method is preferably 20 to 500 m. 2 / g. The proportion of the inorganic fine particles used is preferably 0.01 to 5 mass % of the toner. Specific examples of the inorganic fine particles include silica, alumina, titanium oxide, barium titanate, magnesium titanate, calcium titanate, strontium titanate, zinc oxide, tin oxide, silica sand, clay, mica, wollastonite, diatomaceous earth, chromium oxide, cerium oxide, pengalla, antimony trioxide, magnesium oxide, zirconium oxide, barium sulfate, barium carbonate, calcium carbonate, silicon carbide, and silicon nitride.

[0101] Examples of polymeric fine particles include polystyrene obtained by soap-free emulsion polymerization, suspension polymerization, or dispersion polymerization, methacrylic acid ester or acrylic acid ester copolymers, polycondensation systems such as silicone, benzoguanamine, and nylon, and polymer particles made of thermosetting resins.

[0102] Such fluidizing agents are surface-treated to increase hydrophobicity and prevent deterioration of flow properties and charging properties even under high humidity. Examples of preferred surface treatment agents include silane coupling agents, silylating agents, silane coupling agents having a fluorinated alkyl group, organic titanate coupling agents, aluminum coupling agents, silicone oils, and modified silicone oils.

[0103] Examples of cleaning improvers for removing the developer remaining on the photoconductor or primary transfer medium after transfer include fatty acid metal salts such as zinc stearate, calcium stearate, and stearic acid, and polymer fine particles produced by soap-free emulsion polymerization of, for example, polymethyl methacrylate fine particles, polystyrene fine particles, etc. The polymer fine particles preferably have a relatively narrow particle size distribution and a volume average particle size of 0.01 to 1 μm. EXAMPLES

[0104] The present invention will be described in more detail below by showing examples and comparative examples, but the technical scope of the present invention is not limited to these examples and comparative examples.

[0105] <Synthesis of amorphous polyester resin B-1> In a four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, propylene glycol (biomass-derived alcohol), bisphenol A propylene oxide 2-mol adduct (petroleum-derived alcohol), terephthalic acid, and adipic acid were added in a molar ratio (propylene glycol / bisphenol A propylene oxide 2-mol adduct) of 20 / 80, and terephthalic acid and adipic acid in a molar ratio (terephthalic acid / adipic acid) of 97 / 3. The mixture was charged so that the molar ratio of hydroxyl groups to carboxyl groups, OH / COOH, was 1.3, and flake-shaped polyethylene terephthalate (PET) was added so that it was 50 mass% of the resin component. This was reacted with titanium tetraisopropoxide (500 ppm of the resin component) at normal pressure and 230°C for 8 hours, and then reacted for a further 4 hours at a reduced pressure of 10 mmHg to 15 mmHg. After that, trimellitic anhydride was added to the reaction vessel so that it was 1 mol% of the total resin component, and this was reacted at 180°C, normal pressure, and for 3 hours to obtain [Amorphous Polyester Resin B-1].

[0106] <Synthesis of amorphous polyester resins B-2 to B-5> [Amorphous polyester B-2] to [Amorphous polyester B-5] were obtained by synthesizing the polyesters as described in <Synthesis of amorphous polyester B-1>, except that in <Synthesis of amorphous polyester B-1>, the molar ratio of propylene glycol to 2 mol of bisphenol A propylene oxide adduct and the amount of PET added were changed to the values ​​shown in Table 1.

[0107] [Table 1]

[0108] <Preparation of release agent dispersion W-1> 180 parts of ester wax (NOF Corp., WE-11, synthetic wax made from plant-derived monomers) and 17 parts of an anionic surfactant (Dai-ichi Kogyo Seiyaku Corp., Neogen SC, sodium dodecylbenzenesulfonate) were added to 720 parts of ion-exchanged water. The mixture was dispersed in a homogenizer while heated to 90°C, to obtain [release agent dispersion W-1]. The solid content of the resulting wax particles was 25%.

[0109] <Preparation of release agent dispersion W-2> 180 parts of paraffin wax (HNP-9, manufactured by Nippon Seiro) and 17 parts of an anionic surfactant (Neogen SC, sodium dodecylbenzenesulfonate, manufactured by Daiichi Kogyo Seiyaku) were added to 720 parts of ion-exchanged water. The mixture was dispersed with a homogenizer while being heated to 90°C, to obtain [Release Agent Dispersion W-2]. The solid content of the wax particles obtained was 25%.

[0110] <Preparation of Masterbatch (MB)> 1,200 parts of water, 500 parts of carbon black (Printex35, manufactured by Dexa) [DBP oil absorption=42mL / 100mg, pH=9.5], and 500 parts of [amorphous polyester resin B-1] were added and mixed in a Henschel mixer (manufactured by Nippon Coke and Engineering Co., Ltd.). The resulting mixture was kneaded with two rolls at 150°C for 30 minutes, then cooled by rolling and pulverized with a pulverizer to obtain [master batch MB-1].

[0111] Example 1 <Preparation of resin dispersion> 200 parts of [Release Agent Dispersion W-1] (solid content 50 parts), 750 parts of [Amorphous Polyester Resin B-1], and 100 parts of [Masterbatch MB-1] were placed in a container and mixed at 5,000 rpm for 60 minutes with a TK Homomixer (manufactured by Primix Corporation) to obtain [Resin Dispersion 1].

[0112] <Preparation of aqueous phase> 990 parts of water, 20 parts of sodium dodecyl sulfate, and 90 parts of ethyl acetate were mixed and stirred to obtain a milky white liquid, which was designated as [aqueous phase 1].

[0113] <Emulsification> 700 parts of [Resin Dispersion 1] were stirred at 8,000 rpm with a TK Homomixer while 20 parts of 28% aqueous ammonia were added and mixed for 10 minutes, after which 1,200 parts of [Aqueous Phase 1] were gradually added dropwise to obtain [Emulsified Slurry 1].

[0114] <Solvent removal> [Emulsified slurry 1] was placed in a container equipped with a stirrer and a thermometer, and the solvent was removed at 30° C. for 180 minutes to obtain [solvulant-removed slurry 1].

[0115] <Preparation of shell dispersion> In the preparation of [Resin Dispersion 1], [Release Agent Dispersion W-1], [Amorphous Polyester Resin B-1], and [Masterbatch MB-1] were replaced with [Amorphous Polyester Resin B-5], 720 parts of ion-exchanged water, and 17 parts of anionic surfactant (manufactured by Dai-ichi Kogyo Seiyaku, Neogen SC, sodium dodecylbenzenesulfonate) as a surfactant. The procedure of Example 1 was followed to prepare [Shell Dispersion B-0].

[0116] <Agglutination> 100 parts of 3% magnesium chloride solution was added dropwise to [Solvent-removed Slurry 1] and stirred for another 5 minutes, then the temperature was raised to 60°C. When the particle size reached 5.0 μm, 100 parts of [Shell Dispersion B-0] was added dropwise, and 100 parts of 3% magnesium chloride solution was further added dropwise and stirred for 5 minutes. Then, the temperature was raised to 65°C and 50 parts of sodium chloride were added to finish the aggregation process, thereby obtaining [Aggregated Slurry 1].

[0117] <Fusion> [Agglomerated slurry 1] was heated to 70° C. with stirring, and cooled when the desired average circularity of 0.957 was reached, to obtain [Dispersed slurry 1].

[0118] <Washing and drying> 100 parts of [Dispersion Slurry 1] is filtered under reduced pressure to obtain a filter cake, (1): 100 parts of ion-exchanged water was added to the filter cake, mixed with a TK homomixer (at 12,000 rpm for 10 minutes), and then filtered. (2): 100 parts of a 10% aqueous sodium hydroxide solution was added to the filter cake of (1), mixed with a TK homomixer (at 12,000 rpm for 30 minutes), and then filtered under reduced pressure. (3): 100 parts of 10% hydrochloric acid was added to the filter cake of (2), and the mixture was mixed with a TK homomixer (at 12,000 rpm for 10 minutes) and then filtered. (4): 300 parts of ion-exchanged water is added to the filter cake of (3), mixed with a TK homomixer (at 12,000 rpm for 10 minutes), and then filtered. The above steps (1) to (4) were repeated twice to obtain [Filter Cake 1]. The [filter cake 1] was dried in a circulating air dryer at 45° C. for 48 hours, and sieved through a mesh with 75 μm openings to obtain [resin particle base body 1].

[0119] <External additive processing process> 100 parts of [Resin particle base 1] and 2.0 parts of hydrophobic silica (HDK-2000, manufactured by Clariant) as an external additive were mixed in a Henschel mixer, and passed through a 500 mesh sieve to obtain [Toner 1].

[0120] Toners 2 to 7 were prepared in the same manner as Toner 1, except that the types and amounts of binder resin, release agent, and shell dispersion liquid to be added were changed as shown in Table 2.

[0121] [Table 2]

[0122] Using these toners, the environmental compatibility and durability were evaluated.

[0123] (Evaluation method) <Environmental friendliness> The environmental friendliness of the toner was judged based on the ratio of environmentally friendly resin in the toner, which was calculated from the amount of each raw material added. [Evaluation Criteria] ◎: Non-petroleum monomers and recycled PET account for 40% or more by mass of the total binder resin. ○: The proportion of non-petroleum monomers and recycled PET in the total binder resin is 20% by mass or more and less than 40% by mass. △: The proportion of non-petroleum monomers and recycled PET in the total binder resin is 10% by mass or more but less than 20%. ×: The proportion of non-petroleum monomers and recycled PET in the total binder resin is less than 10% by mass.

[0124] <Durability> After the 100,000-sheet copy test, the toner was removed from the developer by blow-off, and the weight of the remaining carrier was measured and designated as W1. Next, this carrier was placed in toluene to dissolve the molten material, washed, dried, and then the weight was measured and designated as W2. The spent rate was then calculated using the following formula and evaluated. Spent rate [wt%] = [(W1-W2) / W1] x 100 [Evaluation Criteria] ◎: Less than 0.01wt% ○: 0.01wt% or more - less than 0.02wt% △: 0.02wt% or more - less than 0.05wt% ×: 0.05wt% or more

[0125] From the examples in Table 2, it was confirmed that the toners containing propylene glycol, ester wax and PET are excellent in environmental friendliness and durability. In contrast, it was confirmed that the toners obtained in the comparative examples are insufficient in at least one of the environmental friendliness and durability.

[0126] The aspects of the embodiment of the present invention are as follows, for example. <1> Resin particles containing a binder resin and a release agent, The binder resin contains a polyester resin, The polyester resin contains polyethylene terephthalate as a component, The binder resin contains propylene glycol as a diol component, The release agent is an ester wax. Resin particles. <2> The resin particles have a core-shell structure. <1> The resin particles according to claim 1. <3> In the circumferential line on the outermost surface of the resin particle, the line length occupied by the release agent is 5% or less of the total circumferential line length. <1> or <2> The resin particles according to claim 1. <4> The content of propylene glycol in the binder resin is 5% by mass or more based on the total amount of the binder resin. <1> ~ <3> 13. The resin particles according to any one of the above. <5> The propylene glycol in the binder resin is not derived from petroleum. <1> ~ <4> 13. The resin particles according to any one of the above. <6> The polyethylene terephthalate is recycled. <1> ~ <5> 13. The resin particles according to any one of the above. <7> The content of the polyethylene terephthalate is 40% by mass or more based on the total binder resin. <1> ~ <6> 13. The resin particles according to any one of the above. <8> <1> ~ <7> 2. A toner comprising the resin particles according to any one of claims 1 to 11. <9> <8> A developer comprising the toner according to claim 1 and a carrier. <10> <8> A toner storage unit containing the toner according to claim 1. [Explanation of symbols]

[0127] 10 Photoconductor drum 22 Corona charger 40 Developing device 50 Transfer roller 60 Cleaning Equipment 200 Process Cartridge L exposure light P Transfer paper [Prior art documents] [Patent documents]

[0128] [Patent Document 1] JP 2015-025851 A

Claims

1. Resin particles containing a binder resin and a release agent, The binder resin contains a polyester resin, The polyester resin contains polyethylene terephthalate as a component, The binder resin contains propylene glycol as a diol component, The release agent is an ester wax. Resin particles.

2. The resin particle according to claim 1 , wherein the resin particle has a core-shell structure.

3. 3. The resin particle according to claim 1, wherein the length of a circumferential line on the outermost surface of the resin particle, which is occupied by the release agent, is 5% or less of the total circumferential line length.

4. The resin particles according to claim 1 or 2, wherein the content of propylene glycol in the binder resin is 5% by mass or more based on the total amount of the binder resin.

5. The resin particles according to claim 1 or 2, wherein the propylene glycol in the binder resin is derived from a non-petroleum source.

6. The resin particles according to claim 1 or 2, wherein the polyethylene terephthalate is recycled.

7. The resin particles according to claim 1 or 2, wherein the content of the polyethylene terephthalate is 40 mass % or more based on the total binder resin.

8. A toner comprising the resin particles according to claim 1 or 2.

9. A developer comprising the toner according to claim 8 and a carrier.

10. A toner storage unit containing the toner according to claim 8.

Citation Information

Patent Citations

  • Manufacturing method of toner

    JP2015025851A